The Influence of Spiritual Well-Being on Future Anxiety Among Clients of the Malang Probation Office - Ritna Sandri; Indira Ravly Rezaputra; Yo Masapo Krisno Andiko Putro (MOTIVA: JURNAL PSIKOLOGI, 2026)
This research was motivated by the psychological challenges faced by probation clients during the conditional release period, particularly future-related anxiety arising from social stigma, economic uncertainty, and reintegration demands. This research aimed to examine the effect of spiritual well-being on future anxiety among clients of the Malang Probation Office (Balai Pemasyarakatan/Bapas). This research used a quantitative approach with a simple linear regression design involving 104 probation clients selected through convenience sampling. Measures included the Future Anxiety Scale (FAS) developed by Zaleski (1996) and the Spiritual Well-Being Scale (SWBS) proposed by Paloutzian and Ellison (1982). Cronbach’s alpha coefficients of 0.963 for the FAS and 0.883 for the SWBS. The analysis demonstrated a significant negative influence of spiritual well-being on future anxiety (B = -0.345, β = -0.645, t = -8.517, p < .001). Furthermore, spiritual well-being accounted for 41.6% of the variance in future anxiety (R² = .416). The findings indicate that spiritual well-being may function as a protective factor against future anxiety among probation clients. The findings underscore he value of strengthening spiritual well-being as a psychological resource that may enhance emotional adjustment and support successful social reintegration during the conditional release period.